Pelatihan dan Pendampingan Pembuatan Alat Tangkap Bubu bagi Kelompok Nelayan di Desa Tanggetada, Kabupaten Kolaka - Tasabaramo, Ilham Antariksa; Angraini, Yuyun; Asriani, Nenni (Jurnal Pemberdayaan Masyarakat, 2025)
Tanggetada Village has very large potential for marine fishery resources. However, this potential has not been optimally utilized. One of the problems is that the majority of fishermen in the village are small fishermen who have traditional fishing gear with low catch production. Therefore, to increase catch production, this community service activity provides training and assistance to fishermen groups to create fishing gear technology that can increase catch production and is environmentally friendly. The fishing gear used is the Bubu (Fish trap). The partner of the fishermen group in this activity is the Kelompon Nelayan Anak Pesisir of Tanggetada Village. This activity was carried out in August 2024. The activity method was carried out in several stages including the Socialization stage, training and assistance in making Bubu (Fish trap), application of bubu and evaluation of activities. The results of this activity were an increase in the knowledge and skills of fishermen group partners regarding the method of making Bubu, and being able to apply the fishing gear technology.